Staff constructions of the rule-violating behaviour of the institutionalised delinquent child - Potgieter, Rodney Victor (Department of Psychology, 2023)
A ranked repertory grid analysis was used to examine staff constructions of the nature of the institutionalised delinquent child in a reform school. These constructions were assessed as personality attributions made by the staff based upon the rule-violating behaviour of the delinquent boys within the institution. In addition, the manner in which these constructions affect staff decisions with regard to the reprimands they use to manage the rule-violator and whether subgroups of staff differ in this respect, were examined. The Ingrid 72 computer programme was used to analyse the results. It was found that the constructs, Lazy/ Unmotivated and Immature/Irresponsible were the major dimensions used by the staff to differentiate between rule violators at the Reform School. Implications of the staff constructions for the management of the delinquent child showed that custodial aims are still strongly prevalent at the Reform School and that the need to recommend reprimands in a consistent manner receives more emphasis than reprimands based on the nature of the rule-violator.